Projet sur les Jeux Scèniques au Canada Français - Tourangeau, Rémi (Theatre Research in Canada / Recherches théâtrales au Canada, 1991)
The following is a detailed description of a three-year project currently being undertaken by the Groupe de recherche en théâtre populaire at the Université du Québec à Trois-Rivières. The project seeks to explore the phenomenon of large-scale dramatic spectacles usually referred to as Jeux scèniques, ’generally offered as highlights for or accompaniment to popular civic or religious festivals. The precise objectives of the project are described, along with the principal challenges posed and the timetable proposed for attaining them. Methods of socio-historical analysis will be brought to bear both upon the producing agents and upon the productions themselves (dramatic texts and performances), in clear and constant reference to a particular ideological discourse and its translation into real-life experience. The relevancy of this research for better understanding of popular theatre, paratheatre and local festivals is here explored, along with the potential implications of the project for other disciplines. Exposé des principales dimensions d’un programme triennal sur les formes de spectacles à grands effets appelés «jeux scéniques » et présentés dans le cadre des fêtes populaires. Aperçu des objectifs, de la problématique et de la programmation du projet du Groupe de recherche de Trois-Rivières. Avenues d’étude socio-historique d’agents-producteurs (artisans) et de productions scéniques (textes-représentations) autour de la notion du discours idéologique pouvant rendre compte d’un certain discours signifiant du vécu. Incidence d’une telle recherche en regard d’une compréhension du théâtre populaire, du parathéâtre et de la fête populaire. Résultats escomptés par rapport à d’autres disciplines.